Size and shape of Bruch's membrane opening in relationship to axial length, gamma zone, and macular Bruch's membrane defects - Zhang, Qi; Jonas, Jost B. (Investigative ophthalmology & visual science, 2019)
Purpose: To assess axial elongation-associated characteristics in Bruch's membrane opening (BMO) as the inner optic nerve head lamella. - Methods: Participants of the population-based Beijing Eye Study without glaucoma underwent optical coherence tomography for measurement of the BMO size and shape. - Results: The study included 365 individuals (mean age, 61.0 ± 8.7 years; range, 50-88 years; axial length, 24.45 ± 1.99 mm; range, 21.32-30.88 mm). Larger horizontal (mean:1.62 ± 0.28 mm) and vertical (mean: 1.74 ± 0.27 mm) BMO diameters were linearly associated with longer axial length beyond an axial length of 26.0 mm (horizontal diameter: P < 0.001; standardized regression coefficient β: 0.66; nonstandardized regression coefficient B: 0.22; 95% confidence interval (CI): 0.16, 0.27; vertical diameter: P < 0.001; β: 40; B: 0.12; 95% CI: 0.06, 0.18). In multivariable analysis, wider largest gamma zone was associated with larger intrapapillary Bruch's membrane (BM) overhanging on the side opposite to the largest gamma zone (P = 0.006; β: 0.14; B: 0.35; 95% CI: 0.10, 0.60) and with longer horizontal BMO diameter (P < 0.001; β: 0.46; B: 0.59; 95% CI: 0.46, 0.73). The widest BM overhanging location (superior to nasal) was inversely correlated with the widest gamma zone location (inferior to temporal). Within the axial length group of ≥28.0 mm, eyes with macular BM defects had a less markedly increased BMO than those without macular BM defects (2.27 ± 0.18 vs. 2.71 ± 0.41 mm; P = 0.019). The difference between horizontal BMO diameter minus horizontal gamma zone width decreased (P < 0.001) with longer axial length. - Conclusions: Beyond 26.0 mm of axial length, horizontal and vertical BMO diameter increased by 0.21 mm (95% CI: 0.16, 0.27) and 0.12 mm (95% CI: 0.06, 0.18), respectively, for each millimeter of axial elongation. Gamma zone may develop due to an axial elongation-associated BMO enlargement (β: 0.46) and, to a minor degree, a BMO shift in direction to the macula (β: 0.14). A large gamma zone may be protective against myopic macular BM defects.
Gesehen am 12.08.2019